Rho GDP-Dissociation Inhibitor 2 Inhibits C-X-C Chemokine Receptor Type 4-Mediated Acute Lymphoblastic Leukemia Cell Migration - Luo, Jixian; Wang, Junting; Zheng, Huiguang; Wang, Lan (Frontiers in Oncology, 2020)
Although we currently have a good understanding of the role C-X-C chemokine receptor type 4 (CXCR4) plays in T cell acute lymphoblastic leukemia (T-ALL), the mechanism of CXCR4-mediated T-ALL migration remains elusive. Therefore, we focus on the downstream signals of CXCR4 that contribute to T-ALL cell migration in this study. Rho GDP-dissociation inhibitor 2 (RhoGDI2) is expressed preferentially in lymphocytes. It interacts with and regulates the activation of Rho proteins by inhibiting the dissociation of GDP and the binding of GTP. In a previous study, we demonstrated that RhoA and RhoC are activated and required for CXCR4-mediated JURKAT cell migration. In the present work, we investigate the role of RhoGDI2 in CXCR4-mediated T-ALL cell migration. Results show that RhoGDI2 sh2 significantly releases its inhibition effects on T-ALL cell migration toward CXCL12 (C-X-C motif chemokine ligand 12). Phosphorylation of RhoGDI2 on Y24 and Y153 releases RhoA and RhoC from RhoGDI2, which recovers CXCR4-mediated migration toward CXCL12 although the phosphorylation of Y130 has less effect on RhoA or RhoC binding. Furthermore, Src is activated by CXCL12. Transfection of siRNAs to Src reduces CXCR4-mediated migration. Src is required for the phosphorylation of RhoGDI2 on Y153, and ABL1 is activated by CXCL12 and responsible for the phosphorylation of RhoGDI2 on Y24 and Y130. Similarly, knockdown of the expression of ABL1 by siRNAs reduces the CXCR4-mediated migration. Therefore, RhoGDI2 may be a brake for CXCR4-positive T-ALL migration. Because migration is a prerequisite for infiltration of leukemia, this work may suggest the possible involvement of RhoGDI2 in infiltration of T-ALL.